Assessment of Growth, Metallic Ion Accumulation, and Translocation of Lavandin (Lavandula × intermedia) Plant in Cadmium Stress - Halil Samet; Yakup Çıkılı (Journal of Agricultural Sciences)
Excess cadmium (Cd), which is toxic to plants, severely limits crop production in agricultural areas. For this reason, this study investigated the effect of increased Cd levels on lavandin growth, some physiological parameters, and metallic ion accumulation and translocation. In greenhouse conditions, six different levels of Cd (0, 25, 50, 100, 150, and 200 µM Cd) were applied to plants grown in perlite medium together with a complete nutrient solution. Increasing Cd levels decreased biomass production in both the shoots and roots and the contents of chlorophyll (Chl) a, b, a+b, and carotenoid (Car). In addition, excessive Cd decreased the concentrations of some metallic cations such as iron (Fe), zinc (Zn), manganese (Mn), and calcium (Ca) in the shoots and roots. Similarly, increasing Cd decreased the bio-concentration factor (BCF) of the metallic cations (BCF of Cd, Fe, Mn, and Zn in both the shoots and roots and the BCF of copper (Cu) in the roots. Toxic Cd levels decreased the translocation factor (TF) of Zn and Cu and the net accumulation (NA) via roots in Fe and Zn. The effect of Cd on the NA via roots in K, Ca, Mn, and Cu was not found to be significant. However, increasing Cd caused an increase in shoot and root membrane permeability and the TF of Fe and Mn. It was concluded that Cd2+ ion interacts divalent cations such as Ca2+, Fe2+, Zn2+, and Mn2+ ions and could affect the concentrations of these ions in the shoots and roots, and excess Cd has a negative effect on the growth and the photosynthetic capacity of lavandin.